الحماية الإدارية لحقوق الملكية الفكرية في التشريع الجزائري - لقليب, سعد; مخلوفي, عبد الوهاب (جامعة الوادي University of Eloued, 2019)
في إطار سعي الجزائر للانضمام للمنظمة العالمية للتجارة ، عمد المشرع الجزائري إلى إقرار ترسانة من القوانين المتعلقة بحماية حقوق الملكية الفكرية ، لما لها من أهمية وطنية و دولية كذلك ، فذهب إلـى إيجاد آليات متنوعة لحماية حقوق الملكية الفكرية منها القضائية والإدارية ، وعلى هذا الأساس انشا هيئات إدارية متخصصة وأخرى عامة لحماية حقوق الملكية الفكرية ، ونحاول من خلال هذه الورقة البحثية ان نبين الوسائل التي انشاها المشرع لحماية حقوق الملكية الفكرية وتشجيعها ، ومن بين النتائج التي توصلنا اليها ان عدم كفاية الاطار القانونية لحماية الملكية الفكرية ، بل يجب العمل على تجسيدها في الواقع العملي ، والذي سيكون موضوع مقالنا هذا As part of Algeria's bid to join the World Trade Organization (WTO), the Algerian legislator has adopted an arsenal of laws relating to the protection of intellectual property rights because of its national and international importance as well. It has sought to find various mechanisms for the protection of intellectual and intellectual property rights, And through this research paper, we will explore the means that the legislator created to protect and encourage intellectual property rights. Among the results we have reached is the insufficient legal framework for the protection of intellectual property, It must be worked out in practice, which will be the subject of this article.
Keywords: حقوق المؤلف ،حقوق الملكية الصناعية، التسجيل ، حماية المستهلك . حماية الاقتصاد الوطني; Copyright , Industrial Property Rights, registration, consumer protection, Protection of the national economy .